Dilute Hybrid Electrolyte for Low‐Temperature Aqueous Sodium‐Ion Batteries. Issue 23 (26th October 2022) - Sun, Yifei; Zhang, Yan; Xu, Zhao; Gou, Wenshan; Han, Xuguang; Liu, Mengmeng; Li, Chang Ming
Abstract: A hybrid electrolyte based on low‐concentration sodium nitrate with glycerol as an additive was proposed for aqueous sodium‐ion batteries (ASIBs) towards low‐temperature performance. Based on this dilute hybrid electrolyte and configured by bimetallic Prussian blue analogue (Ni2 ZnHCF) cathode and 3, 4, 9, 10‐perylenetetracarboxylic diimide (PTCDI) anode, the full cell demonstrated surprising cycle performance with a specific capacity of 60 mAh g −1 (>800 cycles) and achieved prominent performance at low temperature. Glycerol effectively expanded the electrochemical stability window of the hybrid electrolyte to 2.7 V from formation of strong hydrogen bonds with water molecules and realized the operation of the cell at low temperature, delivering a stable reversible capacity of 40 mAh g −1 at −10 °C. The hybrid electrolyte of glycerol‐water provides a new alternative in development of low‐cost, long‐lifespan, and low‐temperature ASIBs and other aqueous battery systems. Abstract : Baby, it's cold outside : A diluted glycerol‐water hybrid electrolyte with expanding electrochemical stability window of 2.7 V and freezing points below −80 °C is proposed. The introduction of glycerol enables aqueous sodium‐ion batteries with superior cycle stability and low‐temperature performance.